2015
DOI: 10.1590/0103-110420151060003006
|View full text |Cite
|
Sign up to set email alerts
|

Rotatividade da força de trabalho médica no Brasil

Abstract: RESUMO Objetivou-se calcular o índice de rotatividade dos médicos brasileiros. Estudo descritivo, exploratório, quantitativo, realizado por meio de dados secundários, que foram analisados por estatística descritiva. Constatou-se maior índice de rotatividade nas regiões Sudeste e Sul, com médias superiores à nacional (36,7%). A menor média foi evidenciada na região Norte (24,7%). A estratificação por porte populacional aponta para maior rotatividade nos grupamentos de municípios com população entre dez mil e ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
16

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 7 publications
1
13
0
16
Order By: Relevance
“…Those bad conditions at the working place have motivated medical professionals to seek alternatives, thus causing a high turnover of physicians in some regions of the country (PieRANTONi et al, 2015). Moreover, medical specialization becomes inevitable, leading to a higher concentration at specialized centers with high complexity level and available resources for adequate medical practice SANTOS;CAMPOS, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Those bad conditions at the working place have motivated medical professionals to seek alternatives, thus causing a high turnover of physicians in some regions of the country (PieRANTONi et al, 2015). Moreover, medical specialization becomes inevitable, leading to a higher concentration at specialized centers with high complexity level and available resources for adequate medical practice SANTOS;CAMPOS, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A survey conducted by the British Medical Association with 15,560 responses from general practitioners in the UK reported that 34% of practitioners were willing to relinquish practice, reporting that they experienced high levels of work-related stress, and 16% said their stress was significant and uncontrollable 21 . Prolonged periods of overwork may adversely affect the well-being of physicians, leading to manifestations of mental illness, problems in personal relationships, and depression 22 . It is observed that the good interpersonal relationship and the fact that the medical professional likes his work are the main factors associated with satisfaction, as well as the tenure for more than ten years in the local health service.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to regional characteristics of medical turnover, a study carried out by Pierantoni et al 15 showed that the South and Southeast regions had a higher absolute rate of physician turnover, with the Southeast having the highest average rate (62% of professionals). Also, the authors noted that the HDI of this region did not have any relationship with turnover.…”
Section: ; 21(supl1):1325-32mentioning
confidence: 99%